Responsibility of the Regional Government of the Special Capital Region of Jakarta for the Granting of Building Permits on National Vital Objects (Dispute Case of Residents VS PT. Pertamina (Persero) Located in Plumpang) - Wardhani, Dita Yulia Sri; Suryono, Ahmad; Fauziyah, Fauziyah (MIMBAR YUSTITIA : Jurnal Hukum dan Hak Asasi Manusia, 2024)
Land utilization at this time encounters many problems due to the lack of public awareness regarding the importance of ownership of land rights to the attitude of people who are indifferent to their surroundings. This causes conflicts until disputes arise over the utilization of state land by the community. The purpose of this study is to determine the responsibility of the Special Capital Region of the Jakarta Government and the settlement of disputes over the issuance of building permits on land owned by PT Pertamina (Persero) located in Plumpang. The author uses normative juridical research using books, journals, and expert opinions as secondary data sources. This research uses 3 (three) main approaches, namely the statute approach, the conceptual approach, and the case approach. The results of the study are that the Provincial Government of DKI Jakarta is responsible for all risks that may arise as a result of the issuance of IMB for residents around the PT Pertamina Depot in Plumpang as a consequence of the rule of law and democracy. In addition to dispute resolution through the general judicial channel, there are other ways with non-litigation channels or out-of-court channels. Responsibility consists of 2 (two) types, namely political responsibility (responsibility) and legal responsibility (liability). Dispute resolution can be carried out through the litigation route, namely by civil lawsuit and/or state administrative lawsuit and non-litigation route with alternative dispute resolution.